2011
DOI: 10.1590/s1517-83822011000300020
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of Piper diospyrifolium Kunth (Piperaceae) essential oil

Abstract: In vitro activity of the essential oil from Piper diospyrifolium leaves was tested using disk diffusion techniques. The antifungal assay showed significant potencial antifungal activity: the oil was effective against several clinical fungal strains. The majority compounds in the essential oil were identified as sesquiterpenoids by GC-MS and GC-FID techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 3 publications
2
6
0
Order By: Relevance
“…The predominance of sesquiterpenes in leaves has been reported by other authors for the genus Piper (Mesquita et al, 2005;Vieira et al, 2011). While the predominance of phenylpropanoids in roots was the first report in the literature for the species P. aduncum L. The identification of sesquiterpenes in the leaves and phenylpropanoids in roots may be associated with their role.…”
Section: Resultssupporting
confidence: 57%
“…The predominance of sesquiterpenes in leaves has been reported by other authors for the genus Piper (Mesquita et al, 2005;Vieira et al, 2011). While the predominance of phenylpropanoids in roots was the first report in the literature for the species P. aduncum L. The identification of sesquiterpenes in the leaves and phenylpropanoids in roots may be associated with their role.…”
Section: Resultssupporting
confidence: 57%
“…P. arboretum and P. mosenii differed from the others as they had a greater composition of oxygenated sesquiterpene components. Various studies have demonstrated a preference of the Piper species to synthesize sesquiterpenes [28,29,30,31].…”
Section: Resultsmentioning
confidence: 99%
“…The EOs showed significant activity against S. aureus (MIC 780 μg/mL, and for spring MIC, 1560 μg/mL), B. subtilis (MIC 780 μg/mL) and Streptococcus pyogenes (MIC 48–390 μg/mL) [ 37 ]. P. diospyrifolium EO from leaves, composed of cis -eudesma-6,11-diene (21.1%), β-caryophyllene (16.8%), and γ-muurolene (10.6%), was tested using agar diffusion assay and it showed significant potential against clinical fungal strains of C. albicans , C. parapsilosis , C. tropicalis in comparison to nystatin [ 55 ]. P. malacophyllum oil, composed mainly of camphor (32.8%), camphene (20.8%), and ( E )-nerolidol (9.1%), displayed a weak activity against S. aureus , P. aeruginosa , Acinetobacter baumanii (MIC 3700 µg/mL), B. cereus , and E. coli (MIC 1850 µg/mL) using the broth microdilution method [ 56 ].…”
Section: Biological Activitiesmentioning
confidence: 99%
“… Xambioá, Tocantins state, Brazil Aerial parts (HD) Germacrene D (15.2%), curzerene (28.7%), β-bisabolene (5.5%), ( Z )-α-bisabolene (23.2%) --- [ 131 ] P. dilatatum Rich. Carolina, Maranhão state, Brazil Aerial parts (HD) Limonene (19.4%), germacrene D (43.0%), bicyclogermacrene (13.2%) --- [ 131 ] P. diospyrifolium Kunth Universidade de São Paulo, Brazil Leaf (HD) ( E )-Nerolidol (18.2%), spathulenol (25.4%), caryophyllene oxide (7.7%), globulol (6.6%), humulene epoxide II (6.9%) --- [ 35 , 60 ] P. diospyrifolium Kunth Universidade de São Paulo, Brazil Floral (HD) a α-Copaene (47.7%), β-caryophyllene (12.3%), α-humulene (5.7%) --- [ 60 ] P. diospyrifolium Kunth Maringá, Parana state, Brazil Leaf (HD) Limonene (8.5%), ( E )-β-ocimene (5.8%), β-caryophyllene (16.8%), γ-muurolene (10.6%), cis -eudesma-6,11-diene (21.1%), germacrene B (6.2%) Antifungal, agar diffusion assay ( Candida albicans , Candida parapsilosis , Candida tropicalis ) [ 55 ] P. diospyrifolium Kunth Antonina, Paraná state, Brazil Leaf (HD) …”
Section: Table A1mentioning
confidence: 99%